A new species of allobates (Anura: Aromobatidae) from paleovárzea forest in Amazonas, Brazil - Lima, Albertina Pimental (Zootaxa, 2020)
Numerous species of aromobatid frogs in the genus Allobates from the Amazonian region of Brazil have been described in recent years. Herein, we describe a new Allobates from the state of Amazonas. This species is allopatric with three other species of Allobates, two of which we have described previously. The new species inhabits streams in small remnants of paleovárzea forest along margins of a small river, the Paraná do Castanho. Paleovárzeas are ancient floodplains of the Amazon River and its tributaries. Paleovárzea forests are transitional between terra firme forests, which are never flooded, and várzeas, which are seasonally flooded. Males and females of the new species are similar in size; males average 20.1 mm, females 19.8. Tadpoles have a distinct dark brown bar extending from the snout through the eye to midbody. The call of this species consists of quickly repeated groups of single notes and is unique compared to known species of Allobates. Courtship includes cephalic amplexus. Eggs are deposited on the forest floor in cup-shaped leaves in the litter. Unlike other species of Allobates, egg capsules in this species are opaque instead of clear. Copyright © 2010 Magnolia Press.